Starch conversion of ganyong (Canna edulis Ker.) to bioethanol using acid hydrolysis and fermentation - LILY SURAYYA EKA PUTRI; DEDE SUKANDAR (Society for Indonesian Biodiversity, 2008)
Starch of ganyong is one of the sources of ethanol which is able to be produced by acid hydrolysis and fermentation process. It had high concentration of carbohydrate that is 80%, so it could produce glucose highly within acid hydrolysis process. The result showed that the optimal amount of reducing sugar had been produced by nitrate acid 7% (dextrose equivalent, DE = 28.4). Nevertheless, type and concentration of acid had no significantly correlation to reducing sugar yielded. The total amount of glucose had correlation to amount of ethanol, in fermentation process. The optimal amount of ethanol was yielded from 4.81% of glucose and it produced about 4.84% ethanol. The more amount of glucose was yielded the more ethanol was produced. Controlling pH every 12 hours did not affected to production of ethanol significantly.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: bioethanol, Canna edulis Ker, acid hydrolysis, fermentation.